El profesor como mediador intercultural y su papel en la enseñanza de aspectos socioculturales a través de recursos lingüísticos y pragmáticos - Tatoj, Cecylia; Balches Arenas, Rafael Sergio (Neofilolog, 2023)
The learning of a foreign language cannot be carried out in the usual theoretical way, but it is necessary to broaden the scope, focusing on active praxis. In fact, it will be necessary to establish a basis that implies, on the one hand, the implementation of real elements of society and culture in the classroom and, on the other hand, that these elements are based on valid samples, which is what the CEFR-CV currently demands for the effective teaching of a language. Interculturality becomes an invaluable ally, given that in every situation in which it is possible to establish a direct relationship between the teaching of grammar from the perspective of active praxis and the linguistic realizations that result from this teaching action, we must observe that it is necessary to teach a language in which there are no predetermined models, having to attend to the habitual realizations used by native speakers in real interactions in all their variants and fields.